The motorcycle diaries : notes on a Latin American journey - Guevara, Ernesto (Harper Perennian, 2003)
A chronicle of the author's seven-month motorcycle journey throughout South America reveals the beginning of his transformation into a dedicated revolutionary. Special movie tie-in edition of Che Guevara's youthful travel diaries to coincide with the Fall release of Redford & Salles's film of the book. Says director Walter Salles: "If the film reaches a younger audience, I hope it will inspire people to read The Motorcycle Diaries, to have the impression that change can occur." "As his journey progresses, Guevara's voice seem to deepen, to darken, colored by what he witnesses in his travels. He is still poetic, but now he comments on what he sees, though still poetically, with a new awareness of the social and political ramifications of what's going on around him."-January Magazine "The Motorcycle Diaries could easily go on to become the first Spanish language nominee for Best Picture."-Roger Friedman, Fox News.